Karl Barth’s Christological anthropology as a basis for building an interreligious relationship - Y.Y. Putra; A. Himawan; Y.K. Susanta (Acta Theologica)
This article shows that Barth’s Christological anthropology can contribute to conversations about interreligious relations. Using constructive analysis methods, this article begins with an analysis of Barth’s Christological anthropology. A thorough observation of Barth’s Christological anthropology reveals that his theology provides a potential basis for a theological concept of interreligious relations. The theological concept of interreligious relations, based on Barth’s Christological anthropology, affirms that the most fundamental commonality between Christians and other religious people lie in the fact that they are God’s chosen human beings in Jesus Christ as partners of the covenant with God and with others. This theological concept of interreligious relations can guide Christians in relating to other religious groups, while they can also remain faithful to witness Jesus Christ as the centre of the message of true humanity.